Musical Imagery - Godøy, Rolf Inge; Jorgensen, Harald (Lisse Swets & Zeitlinger, 2001)
An edited collection of papers which explore a large number of topics related to musical imagery. Musical imagery can be defined as our mental capacity for imagining sound in the absence of a directly-audible sound source, meaning that we can recall and re-experience or even invent new musical sound through our "inner ear". The first part of the volume is focused on theoretical issues such as the history, epistemology, neurological bases, and cognitive models of musical imagery. The second part presents various applications of musical imagery in performance and composition, and provides the reader with a broad overview of the many musical activities which are concerned with musical imagery. Musical imagery is a truly interdisciplinary subject, and it is the belief of the editors that a plurality of approaches, ranging from the introspective and philosophical to the experimental and computational, is the most fruitful strategy for exploring the subject of musical imagery.